How green growth is adopted by local policy – a comparative study of ten second-rank cities in Sweden. (2nd October 2018) - Hermelin, Brita; Andersson, Ida
ABSTRACT: The 1992 Rio Earth Summit represented a crucial point in time at which the key role of the local level for sustainable development was importantly endorsed. However, since this UN summit, ideals about how to design local sustainable development have changed significantly. This paper investigates how local policy in ten second-rank cities in Sweden has adopted decoupling arguments and endorsed green growth concepts established through international governance communities. Using content analysis of politically ratified steering documents in these cities, the main findings suggest that local strategising related to the policy goals of green growth is mainly related to energy efficiency. Derived from the decoupling argument, one factor behind shallow integration of green growth into municipal policy is that green growth could be considered a political and contested concept. The fact that there has been limited implementation of this framework across the investigated municipalities prompts reflections on how the results could be explained by institutional 'match' or 'mismatch' between local institutional environments for policy interventions and the green growth concepts promoted by international communities. The adoption of green growth concepts requires local authorities to broaden their commitment for interventions in interactions with industry and business.